Wasei-eigo in EFL Writing: A Case Study of Japanized English Production Among Native Japanese Learners - Alex Jhon; Momoko Takai (GLENS: Global English Insights Journal, 2026)
EFL speakers from the Asian continent use English as a means of daily communication. From all these rich cultured Asian countries, there are many fascinating English varieties, one of the distinctively well-known is the Japanese English register which can be found only in Japan. This study aims to examine whether the Japanized English variety can be acceptably validated within the discourse of English language acquisition. The scope of this study is within the concepts of creative writing learning, constructing process and World English. The respondents were five Japanese EFL learners with an overall TOEFL iBT scored at least 79 points or IELTS scored at least 6.5. The data being used were the written outputs from the respondents. The analysis of these creative outputs suggested that wasei-eigo serves as a legitimate and functional variety of English, particularly within its "natural habitat" of Japan. The findings showed that such localized registers can be accepted as valid linguistic productions rather than mere errors. Ultimately, the study advocates for a reconfigured interface of World English paradigm, highlighting the need for a more inclusive understanding of English proficiency that honors the diverse sociocultural identities of Asian speakers.